Kulturowe studia nad prawem autorskim - Jakubowiak, Maciej (Er(r)go. Teoria - Literatura - Kultura, 2016)
Maciej Jakubowiak Uniwersytet Jagielloński, Wydział Polonistyki, Katedra Antropologii Literatury i Badań Kulturowych Cultural Studies on Copyright Law The goal of the article is to present and analyze the key problems of cultural studies on copyright law – a relatively new area of literary and cultural research, developed mostly in the United States since 1980s. The main objective of thus oriented research is to introduce an alternative perspective to studies traditionally carried out by copyright lawyers – a perspective allowing one to recognize the complexity of ways in which legal solutions may impact cultural practice. The article chronologically discusses the most important publications representing this subdiscipline, including text by such authors as Martha Woodmansee, Mark Rose, Paul K. Saint-Amour and Caren Irr. The critical presentation of the material focuses on ways of defining relations between copyright law and literature, on the impact of analyses carried out within this model upon our understanding of the cultural phenomena under discussion, and – last but not least – on research methods within the area. Additionally, the argument presented in the article serves the purpose of deriving a more general formula of thinking about literature from the existing research and of confronting it with other modes of reflection about the relations obtaining between various disciplines of academic research. Keywords: cultural studies on copyright law, copyright, authorship, impact of legal solutions upon cultural practice Kulturowe studia nad prawem autorskim Artykuł poświęcony jest prezentacji i analizie najważniejszych problemów formułowanych w ramach kulturowych studiów nad prawem autorskim – nurcie badań literaturo- i kulturoznawczych rozwijających się głównie w Stanach Zjednoczonych od lat 80. XX wieku. Głównym celem tych badań jest wprowadzenie odmiennej perspektywy do zarezerwowanych tradycyjnie dla prawoznawców studiów nad prawem autorskim, pozwalające na odsłonienie złożonych sposobów, na jakie rozwiązania prawne przekładają się na praktyki kulturowe. W artykule analizowane są w porządku chronologicznym najważniejsze publikacje tego nurtu badawczego, autorstwa m.in. Marthy Woodmansee, Marka Rose’a, Paula K. Saint-Amoura i Caren Irr. Krytyczna prezentacja materiału bierze pod uwagę takie kwestie, jak: sposoby definiowania relacji między prawem autorskim a literaturą; efekty prowadzonych analiz dla rozumienia omawianych fenomenów kulturowych; projektowane metody badawcze. Dodatkowym celem artykułu jest próba wypreparowania z przedstawianych badań ogólniejszej formuły myślenia o literaturze i skonfrontowanie jej z innymi sposobami myślenia o relacjach między dyscyplinami naukowymi. Słowa kluczowe: kulturowe studia nad prawem autorskim, copyright, prawo autorskie, autorstwo, wpływ rozwiązań prawnych na praktykę kulturową